Основні підсумки та завдання вивчення Пастирського городища - Приходнюк, О.М. (Археологія, 1998)
Стаття присвячена підсумкам та основним завданням вивчення Пастирського городища. Сто лет назад, в 1898 г. известный украинский археолог В. В. Хвойка на территории Среднего Поднепровья начал археологические исследования Пастырского городища, которые со значительными интервалами продолжили С. В. Коршенко, И. В. Фабрициус, М. Ю. Брайчевский, О. М. Приходнюк. Этими работами было установлено, что Пастырское в раннесредневековое время было ремесленным центром, где работали высококвалифицированные гончары, кузнецы, ювелиры. Истоки пастырского ремесла прослеживаются в производственных и художественных традициях Нижнего Подунавья. Пастырское городище, вместе с другими археологическими памятниками (городище Бжецлав-Поганско и клад из Земянского Врбовка в Словакии, клады из Залесья в Среднем Поднестровье и Харивки в Среднем Поднепровье и др.) являются свидетельством отселений славян в конце VI в. из Подунавья, куда они попали вследствие колонизационных движений VI—VII вв. Такие отселения были вызваны приходом туда болгар Аспаруха в 680 г., которые стали угнетать коренное население. Этим передвижениям Нестор придал ключевое значение в истории славян, сформулировав дунайскую теорию их происхождения. Вернувшиеся на свою прародину в Среднее Поднепровье, славяне на Пастырском городище обновили скифские ров и вал, укрепив его дополнительно деревянно-земляной оборонительной стеной. Построили там жилища-полуземлянки славянского облика (50 из которых раскопаны археологами), кузницу. К сожалению, остаются пока не обнаруженными гончарные и бронзолитейные мастерские. Особый интерес вызывает частично исследованные остатки четырех длинных сооружений, которые вместе с тремя линиями валов отделяли юго-западную часть городища на площади 0,5 га. Не исключено, что эта территория была местом расположения общинного двора или двора вельможи. Однако, на этот вопрос, как и на многие другие можно будет ответить лишь после осуществления дополнительных раскопок Пастырского городища, территория которого подвергается разрушениям, а потому требует принятия срочных мер по ее защите со стороны государства. One hundred years ago, in 1898, V.V. Khvoyka, the well-known Ukrainian archaeologist, began to investigate Pastyr Settlement in the Middle Dnieper. S.V. Korshenko, I.V. Fabritsius, M.Yu. Brayehevsky and O.M. Prykhodnyuk have continued his investigation. Due to these works it was established that Pastyr Settlement was a craft center where the high skilled potters, blacksmiths and jewelers had been worked. The art style and production traditions of Pastyr Settlement are of the Lower Danube origin. Pastyr Settlement, along with other archaeological sites (Bzheslav-Pogansko Settle¬ment, hidden treasures from Zemianky Vrbovka in Slovak, Zalissia in the Middle Dniester and Khariivka in the Middle Dnieper, etc.) testify that at the end of 7th century, Slavs gradually migrated from Danube territories (their previous location) due to colonization movements in 6th and 7th century. They were stimulated to migration by the invasion of Asparuch’s Bulgarians to that territory in 680, who began to suppress the native population. Nestor the Chronicler attached particular significance to these migrations in the history of Slavs and developed the Danube concept of Slavs origin. On returning to their fore-motherland in the Middle Dnieper, the Slavs had renewed the Scythian moat and rampart in Pastyr Settlement and fortified them with additional wooden and earthen fortifications. They built there the semi-deepened dwellings of Slavonic type (fifty of them have been investigated by archaeologists) and smithy. Unfortunately, the pottery and bronze casting workshops were not yet found in the Settlement. The remains of four long constructions that (along with three lines of ramparts) separated over 0,5 hectares in southwest part of the Settlement have partially been investigated. It is not inconceivable that a community place or yard of a noble man was located there. But this point has not been finally established. The point invites further investigation in Pastyr Settlement. As of now, the territory of the Settlement is prone to damage and therefore, it requires that urgent measures be taken by state to protect this territory.